A Protestant vision: William Harrison and the reformation of Elizabethan England - Parry, G. (Cambridge studies in the history and theory of politics, 1987)
This book deals with the thought of William Harrison, a well-known Elizabethan intellectual, whose ideas are significant chiefly because they are often representative of the thoroughgoing Protestantism which adapted continental reformed ideas to the circumstances of Tudor England. The book explains how the mentality of Harrison, a university-trained Protestant, reveals a coherent worldview based upon a particular view of history which he applied to many areas of contemporary concern: the complete reformation of the church, the improvement of society, the removal of economic injustice, the reorientation of practical life and the restraint of the dangerous speculation current in natural philosophy. Dr Parry draws upon a unique and previously unknown manuscript source, Harrison's interpretation of world history, which provides unusually detailed information about how one individual interpreted the world.